Isolamento de DNA genômico em amostras foliares de Nectandra megapotamica (Spreng.) Mez. (Lauraceae) - Costa, Leonardo Severo da (2014)
Nectandra megapotamica (Spreng.) Mez is a native tree species of ecological and pharmacological importance, due to its great potential for the production of drugs. The selection of genetically superior individuals is a feasible alternative to leverage the studies regarding this potential. However, because it is a species that produces large amounts of secondary metabolites, the isolation of genomic DNA in sufficient quantities and of good quality, is crucial step for the development of any technique for direct analysis of deoxyribonucleic acid. Considering the above, the overall objective of this study was to define a protocol for DNA extraction, specific to Nectandra megapotamica (Spreng.) Mez. Able to obtain samples of quality and quantity for further applications. The foliar samples dried at room temperature, dried in oven at 40 °C and dried in a microwave oven, plus four DNA extraction protocols were tested (Dellaporta, Ferreira and Grattapaglia, Khanuja e Mazza and Bittencourt). The ratios A260/A230, A260/A280, the concentration of DNA obtained, DNA integrity, functionality DNA via digestion with Hind III enzyme and the correlation between the expected absorbance curve for a DNA sample and the observed curve were evaluated. For the types of foliar samples was found that it is possible to extract DNA from both. However, only dried at room temperature samples showed results for quality and quantity as expected. In the analysis of different extraction protocols, Mazza and Bittencourt and Ferreira and Grattapaglia showed the best results for DNA concentration. However, these exhibited high levels of contamination, verified by the gelatinous aspect and brown coloration the end of the procedure, confirming the results indicated by ratios. Correlation analysis of the absorbance curve for these two protocols showed that the absorbance peaks were 220 nm and 245 nm, respectively, indicating high levels of phenolic compounds or polysaccharides in the samples. The Dellaporta protocol, showed the best results for two reasons, one concentration of intermediate DNA, the highest correlation between expected and observed DNA curve. In addition the extracted DNA was digested by the enzyme Hind III, which was not observed for other protocols. With the intention to optimize the Dellaporta protocol, tests were performed with different concentrations of SDS (10, 15, 20 and 25%), PVP (0, 1, 2 and 3%), potassium acetate (2,5; 5; 7,5 and 10 M) and NaCl in the elution buffer (0, 0,5; 1 and 1,5 M), wherein the DNA concentration, the A260/A280 and A230/A230 ratio and the correlation between the absorbance curves were evaluated. Tests with NaCl in the elution buffer and Potassium Acetate have not resulted significant gains, indicating their respective use according the original protocol. For SDS, concentrations of 15 and 25% the greatest amount of extracted DNA. However, 15% presented a ratio A260/A230 lower than expected. Regarding PVP, in absence and presence of 1% concentration presented very close results, however, the latter showed greater correlation between the absorbance curves. The combined analysis of all variables, indicated that the use of 25% SDS and 1% PVP in Dellaporta protocol, contributes to improve concentration and quality of isolated DNA.